Pengaruh Self Service Technology (SST) Terhadap Kepuasan Nasabah Bank Umum Syariah - Hasanah, Wihayatun; Isnandar, Fajri Ryan (LPPM Universitas Islam 45, 2024)
This research aims to explain the influence of Self Service Technology on the satisfaction of customers of Sharia Commercial Banks. The variables used in this study are two independent variables, X1 ATM and X2 Mobile Banking. The method used is a quantitat4e method with data collection through the distribution of questionnaires to customers of Sharia Commercial Banks who use Self Service Technology. The sampling technique used in this research is purpos4e sampling, with a sample size of 100 respondents. The focus of this research is on students of Un4ersitas Islam 45 Bekasi who have accounts in Sharia banks and use Self Service Technology. Instrument testing is conducted using validity and reliability tests. Data analysis is performed using classic assumption tests and hypothesis testing with multiple linear regression. The results of this study indicate that ATM and Mobile Banking services have a posit4e impact on the satisfaction of customers of Sharia Commercial Banks. This is because customers who use ATM services usually use them for cash withdrawals, while Mobile Banking is commonly utilized for transactions other than cash withdrawals because it can be done anywhere and anytime.